2022
DOI: 10.1186/s13018-022-03162-w
|View full text |Cite
|
Sign up to set email alerts
|

Roxadustat promotes osteoblast differentiation and prevents estrogen deficiency-induced bone loss by stabilizing HIF-1α and activating the Wnt/β-catenin signaling pathway

Abstract: Background Osteoporosis is a very common skeletal disorder that increases the risk of fractures. However, the treatment of osteoporosis is challenging. Hypoxia-inducible factor-1α (HIF-1α) plays an important role in bone metabolism. Roxadustat is a novel HIF stabilizer, and its effects on bone metabolism remain unknown. This study aimed to investigate the effects of roxadustat on osteoblast differentiation and bone remodeling in an ovariectomized (OVX) rat model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This indicates that the inhibition of HIF-1α may promote osteoblast proliferation and activity, contributing to an anti-osteoporotic effect. Conversely, Li et al [ 50 ] reported that raloxifene significantly increased the ALP staining intensity in osteoblasts by upregulating the protein expression of HIF-1α and β-catenin in OVX rat bone tissue. This indicates that the anti-osteoporotic effect of raloxifene is associated with the activation of HIF-1α and enhanced osteoblast proliferation, which challenges the findings of Chen et al Given these conflicting outcomes, the role of the HIF-1α signaling pathway in osteogenic activity during osteoporosis treatment requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the inhibition of HIF-1α may promote osteoblast proliferation and activity, contributing to an anti-osteoporotic effect. Conversely, Li et al [ 50 ] reported that raloxifene significantly increased the ALP staining intensity in osteoblasts by upregulating the protein expression of HIF-1α and β-catenin in OVX rat bone tissue. This indicates that the anti-osteoporotic effect of raloxifene is associated with the activation of HIF-1α and enhanced osteoblast proliferation, which challenges the findings of Chen et al Given these conflicting outcomes, the role of the HIF-1α signaling pathway in osteogenic activity during osteoporosis treatment requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that activating the HIF-1 signaling pathway can improve bone mineral density and promote osteoblast differentiation in OVX rats. [ 22 ] Additionally, HIF-1 is a crucial molecule that mediates bone-vascular interaction, and up-regulating the HIF-1 signaling pathway can promote angiogenesis and alleviate bone loss in ovariectomized (OVX) mice. [ 21 , 23 ] VEGF is a crucial regulator of angiogenesis that plays a significant role in bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the HIF signaling pathway plays an important role in bone formation during fracture repair. Conditional deletion of HIF-1 or HIF-2 in osteoblasts results in a significant reduction in bone volume, whereas HIF-1 and HIF-2 are over-stabilized by the loss of VHL, leading to increased bone mass and thus changes in bone volume [ 43 , 44 , 45 ].…”
Section: The Hypoxic Microenvironment Of Bonementioning
confidence: 99%